Nonlinear Spectral‐Imaging Study of Second‐ and Third‐Harmonic Enhancements by Surface‐Lattice Resonances. Issue 8 (20th February 2020) - Shen, Binglin; Liu, Liwei; Li, Yanping; Ren, Sheng; Yan, Junshuai; Hu, Rui; Qu, Junle
Abstract: An ultrafast spectral imaging optical system featuring adaptive precompensation for group delay dispersion, automated tuning and collimation, rapid power stabilization, and rapid spectral imaging switching is developed. In this system, real‐time visualization ensures that the excited Gaussian beam remains focused on the nanoarray of the electron‐beam lithographed metasurface, as well as maximum gain of the nonlinear effect information. Based on the system, two surface‐lattice resonance metasurfaces under broadly tunable excitation (800–1300 nm) are investigated. The results demonstrated a 16‐fold enhancement in the third harmonic generation intensity and a 168‐fold enhancement in the second harmonic generation intensity at a 1200 nm excitation compared to the unpatterned films, with a narrow resonant bandwidth of 8 nm. This can be attributed to the frequency‐matching lattice‐enhanced localized surface plasmon resonance, which results in effective and vast excitation of plasmons that produce numerous energetic carriers. The method offers the possibility to reveal various ultrafast dynamics in nonlinear plasmonic metasurfaces. Abstract : This study presents an ultrafast spectral imaging optical system, featuring precompensation for group delay dispersion and autoregulations, to investigate two surface‐lattice resonance metasurfaces under near infrared (NIR) I and II excitation. A 16‐fold enhancement in the third harmonic generation intensity and a 168‐fold enhancement in the second harmonic generation intensity at a 1200 nm excitation are demonstrated as compared to unpatterned films.